Analysis of CdTe photovoltaic cells for ambient light energy harvesting - Mathews, Ian; Kantareddy, Sai Nithin Reddy; Liu, Zhe; Munshi, Amit; Barth, Kurt; Sampath, Walajabad; Buonassisi, Tonio; Peters, Ian Marius (Journal of Physics D: Applied Physics, 2020)
This paper investigates the suitability of CdTe photovoltaic cells to be used as power sources for wireless sensors located in buildings. We fabricate and test a CdTe photovoltaic cell with a transparent conducting oxide front contact that provides for high photocurrents and low series resistance at low light intensities and measures the photovoltaic response of this cell across five orders of magnitude of AM1.5G light intensity. Efficiencies of 10% and 17.1% are measured under ∼1 W m-2 AM1.5G and LED irradiance respectively, the highest values for a CdTe device under ambient lighting measured to date. We use our results to assess the potential of CdTe for internet of things devices from an optoelectronic, as well as a techno-economic perspective, considering its established manufacturing know-how, potential for low-cost, proven long-term stability and issues around the use of cadmium.
CRIS-Team Scopus Importer:2022-06-05
Keywords: CdTe; energy harvesting; internet of things; photovoltaics; solar cell; wide bandgap